(untitled) (Research, Society and Development, 2022)
Objective: To assess the perception and preventive attitudes of dentists in the state of Paraíba in relation to COVID-19. Methodology: This is a cross-sectional study, with application of a semi-structured questionnaire to dentists registered at the Regional Council of Dentistry of Paraíba. Data were analyzed using SPSS software. Results: 227 dentists participated, most of them women (70.4%), aged between 22-30 years (47.1%), with training time between 1 to 5 years (35.2%), with a master’s degree (33.9%) and working in the public and private sectors (42.3%). 87.7% of respondents reported complying with social isolation and 88.1% reported having suspended elective dental care during the pandemic. Regarding the procedures that should be performed during the pandemic, the treatment of dental abscess (90.7%), dental trauma (80.1%) and suture removal (61.7%) were the most cited. In addition, it was observed that before the pandemic, N95 and FFP2 masks were used by 9.3% and 8.4% of dentists, respectively, and that during the pandemic, this percentage increased to 36.9% (N95) and 34.6% (FFP2). Regarding the use of face shields, the percentage of use before and during the pandemic was 37.4% and 76.9%, respectively. Conclusions: The knowledge of dentists was considered consistent in relation to preventive practices of dental care in the COVID-19 period. However, despite participating in capitation courses on COVID-19, participants showed insecurities when caring for patients with suspected disease.